The Influence of PBL and PjBL Models and Learning Motivation on Science Learning Outcomes - Aziziah; Rufi’i; Retno Danu Rusmawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the influence of the Problem Based Learning (PBL) and Project Based Learning (PjBL) learning models and learning motivation on the science learning outcomes of class IX students at SMPN 1 Pacet. The study employed an experimental method with a 2×2 factorial design. The research sample consisted of two randomly selected classes, each with 30 students. The research instruments included a science learning achievement test and a learning motivation questionnaire, both of which had been tested for validity and reliability. The data were analyzed using a two-way ANOVA after meeting the assumptions of normality and homogeneity. The results showed that the learning model significantly influenced science learning outcomes (Sig. = 0.000). Students learning using PjBL showed greater improvement in learning outcomes than those using PBL. Learning motivation also significantly influenced learning outcomes (Sig. = 0.000), with students learning through PjBL demonstrating higher learning outcomes than those learning through PBL. Furthermore, there was a significant interaction between the learning model and learning motivation on science learning outcomes (Sig. = 0.016), indicating that the effectiveness of the learning model depends on students’ levels of learning motivation. In conclusion, these findings emphasize the importance of selecting an appropriate learning model and the need to consider motivational factors to optimize science learning outcomes.